(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to investigate the relationship between psychological flow and electronic violence among adolescent gamers in Saudi Arabia. The research was conducted on a sample of 450 male and female teenagers, to investigate the differences in the levels of psychological flow and electronic violence based on the following variables, family status (living with both parents, living with one parent, living with relatives), and age (12-21 years old). Descriptive cross sectional study was conducted using a self-structured questionnaire consisted from 27 questions about psychological flow and 8 questions about electronic violence, answered on a Likert scale ranging from strongly disagree to strongly agree. results: There was no significant relationship between the psychological flow scale and the electronic violence scale among adolescent gamers in Saudi Arabia. Additionally, the results showed no statistically significant differences in the mean scores of adolescent gamers’ psychological flow based on age and family status, as well as no statistically significant differences in the mean scores of adolescent gamers’ electronic violence based on age and family status.